40. ANALYSIS OF SOCIAL RELATIONS IN THE WORK OF ABU NASR FARABI FROM A DIALECTICAL POINT OF VIEW - Salimov Bahriddin Lutfullaevich, Yunusov Sodiq Sabirjonovich (Innovative technologies in construction Scientific Journal, 2023)
Abu Nasr Farabi also emphasizes that people living in society have different characteristics, knowledge and worldviews: "There are more or less differences and differences even in the most famous ideas of certain peoples about a certain type of people. Because every nation realizes that thing and event in its own way and reflects it.